Chapter Bruno Trentin e l'Europa tra comunicazione politica e rappresentazioni mediatiche - Attolini, Grazia Pia (Studi e saggi, 2023)
Bruno Trentin's studies on political communication are neither unitary nor exhaustive, that's why his research is original and innovative. Through the investigation of different communication contexts it is possible to reconstruct lexicon, rhetoric, narration, visual identity, relationship with the media. Far from the tones of the average union leader, Trentin remains faithful to his composed and philosophical attitude and, by so doing, successfully involves and fascinates masses, the television audience, readers, and even activists and fellow party members. The linguistic and communication strategies he uses differ not only from the traditional trade union leadership but also from politics. In Trentin's studies the substance of the message definitely prevails on the aesthetics of the form.